Air pollution in relation to very short-term risk of ST-segment elevation myocardial infarction: Case-crossover analysis of SWEDEHEART - Sahlen, Anders (ELSEVIER IRELAND LTD, 2021)
10.1016/j.ijcard.2018.10.069